Let all know: insights from a digital storytelling facilitator training in Uganda - Tingting Yan; Michael Lang; Teddy Kyomuhangi; Barbara Naggayi; Jerome Kabakyenga; Wasswa William; Scholastic Ashaba; Clementia Murembe Neema; Manasseh Tumuhimbise; Robens Mutatina; Deborah Natumanya; Jennifer L. Brenner (Taylor & Francis Group, 2021)
Background Digital storytelling (DST) is a participatory, arts-based methodology that facilitates the creation of short films called digital stories. Both the DST process and resulting digital stories can be used for education, research, advocacy, and therapeutic purposes in public health. DST is widely used in Europe and North America, and becoming increasingly common in Africa. In East Africa, there is currently limited in-country DST facilitation capacity, which restricts the scope of use. Through a Ugandan-Canadian partnership, six Ugandan faculty and staff from Mbarara University of Science and Technology participated in a pilot DST facilitation training workshop to enhance Ugandan DST capacity. Objective This Participatory Action Research (PAR) study assessed the modification of DST methodology, and identified the future potential of DST in Uganda and other East African settings. Methods In the two-week DST Facilitator Training, trainees created their own stories, learned DST technique and theory, facilitated DST with community health workers, and led a community screening. All trainees were invited to contribute to this study. Data was collected through daily reflection and journaling which informed a final, post-workshop focus group where participants and researchers collaboratively analyzed observations and generated themes. Results In total, twelve stories were created, six by trainees and six by community health workers. Three key themes emerged from PAR analysis: DST was a culturally appropriate way to modernize oral storytelling traditions and had potential for broad use in Uganda; DST could be modified to address ethical and logistical challenges of working with vulnerable groups in-country; training in-country facilitators was perceived as advantageous in addressing community priorities. Conclusion This pilot study suggests DST is a promising methodology that can potentially be used for many purposes in an East African setting. Building in-country DST facilitation capacity will accelerate opportunities for addressing community health priorities through amplifying local voices.